2015
DOI: 10.1002/2015gl064871
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the ionospheric impact of tsunami‐driven gravity waves with SAMI3: Conjugate effects

Abstract: The Naval Research Laboratory first‐principles ionosphere model SAMI3 is used to study the ionospheric effects associated with tsunami‐driven gravity waves. Specifically, the Tohoku‐Oki tsunami of 11 March 2011 is modeled. It is shown that gravity wave‐induced variations in the neutral wind lead to plasma velocity variations both perpendicular and parallel to the geomagnetic field. Moreover, the electric field induced by the neutral wind perturbations can map to the conjugate hemisphere. Thus, electron density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 25 publications
4
63
1
Order By: Relevance
“…When the conductivity variations are included, polarization electric field will occur. The numerical simulations of Huba et al [] show that polarization electric field is indeed generated by tsunami‐driven gravity waves. The gravity waves cause plasma velocity variations both perpendicular and parallel to the geomagnetic field, and the polarization electric field is transmitted to the magnetically conjugate region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the conductivity variations are included, polarization electric field will occur. The numerical simulations of Huba et al [] show that polarization electric field is indeed generated by tsunami‐driven gravity waves. The gravity waves cause plasma velocity variations both perpendicular and parallel to the geomagnetic field, and the polarization electric field is transmitted to the magnetically conjugate region.…”
Section: Discussionmentioning
confidence: 99%
“…These observed electric fields, corresponding to plasma drifts of several tens of meters per second perpendicular to the magnetic field, are assumed to have been amplified by the Perkins instability. In contrast, the E × B drifts generated within gravity wave‐induced perturbations at low latitudes, without involving the Perkins instability, in numerical simulations are only a few meter per second [ Huba et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…MAGIC solves the Euler equations via the f wave method of Bale et al (2003) in a modified version of Clawpack 4.2 (Clawpack Development Team, 2002;LeVeque, 2002), with time-split solutions for Navier-Stokes viscosity and thermal conduction. GEMINI uses the same mathematical formulation as Zettergren and Snively (2015, Appendix A) except for that the electrodynamic problem is changed slightly; the large number of grid points needed for this study makes both direct and iterative solutions inefficient, so we adopt an equipotential field line (EFL) approximation, which uses a field-integrated version of the current continuity equation (e.g., Huba et al, 2015). GEMINI uses the same mathematical formulation as Zettergren and Snively (2015, Appendix A) except for that the electrodynamic problem is changed slightly; the large number of grid points needed for this study makes both direct and iterative solutions inefficient, so we adopt an equipotential field line (EFL) approximation, which uses a field-integrated version of the current continuity equation (e.g., Huba et al, 2015).…”
Section: Numerical Modeling Basismentioning
confidence: 99%
“…Huba et al (2015) have reported the ionospheric effect associated with tsunami-driven gravity waves; the wind perturbations of gravity waves could produce polarization electric fields transmitting along the geomagnetic field lines to the ionospheric F region and the conjugate hemisphere. It is difficult for a short-period gravity wave propagating upward to the upper atmosphere since the buoyancy periods are quite large.…”
Section: Sami3/esf Model Simulationsmentioning
confidence: 99%